Modeling Myeloid Malignancies Using Zebrafish - Potts, Kathryn S.; Bowman, Teresa V. (Frontiers in Oncology, 2017)
Human myeloid malignancies represent a substantial disease burden to individuals, with significant morbidity and death. The genetic underpinnings of disease formation and progression remain incompletely understood. Large-scale human population studies have identified a high frequency of potential driver mutations in spliceosomal and epigenetic regulators that contribute to malignancies, such as myelodysplastic syndromes and leukemias. The high conservation of cell types and genes between humans and model organisms permits the investigation of the underlying mechanisms of leukemic development and potential therapeutic testing in genetically pliable pre-clinical systems. Due to the many technical advantages, such as large-scale screening, lineage-tracing studies, tumor transplantation and high-throughput drug-screening approaches, zebrafish is emerging as a model system for myeloid malignancies. In this review, we will discuss recent advances in MDS and leukemia using the zebrafish model.